2015
DOI: 10.1136/archdischild-2015-308664
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal EEG and neurodevelopmental outcome in preterm infants born before 32 weeks

Abstract: Of the 1744 infants assessed at 2 years, 422 had a non-optimal outcome. A total of 4804 EEGs were performed, and 1345 infants had at least one EEG. EEG abnormalities were predictive of non-optimal outcomes after controlling for confounding factors such as severe intracranial lesions detected by brain imaging. Transient moderate and severe abnormalities were independent predictors of non-optimal outcomes with an OR and 95% CI of 1.49 (1.08 to 2.04) and 2.38 (1.49 to 3.81), respectively. In the validation group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…Pioneering studies have shown that the EEG provides valuable prognostic information in preterm infants [32,[43][44][45][46][47][48][49][50] , and this has been confirmed by other more recent studies [25,[51][52][53][54][55][56][57] .…”
Section: Introductionsupporting
confidence: 54%
“…Pioneering studies have shown that the EEG provides valuable prognostic information in preterm infants [32,[43][44][45][46][47][48][49][50] , and this has been confirmed by other more recent studies [25,[51][52][53][54][55][56][57] .…”
Section: Introductionsupporting
confidence: 54%
“…Some developmental scales only provide an overall general developmental quotient, such as the Griffith's developmental scales, which was used in three studies, and the Brunet–Lézine test used in the study of Perivier et al …”
Section: Resultsmentioning
confidence: 99%
“…24,25,29,[38][39][40] Infants included in the follow-up had significantly (p<0.05) lower mean birthweight 25,29,38 and gestational age, 25,38,40 and were more severely ill (days on mechanical ventilation, 25,29 sepsis, 25,29,38 infection, 24,40 bronchopulmonary dysplasia, 25,39 chorioamnionitis, 24 chronic lung disease, 38 and inferior neuromotor examination at discharge). 40 Two studies observed differences in maternal characteristics. 24,39 Delmas et al 24 found non-significant differences between both groups with respect to higher maternal education (60% in the follow-up group and 35.3% for the lost-to-follow-up group, p=0.074); and in the study of Patra et al, 39 mothers were slightly younger in the lost-to-follow-up group (not significant).…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Electroencephalography (EEG) is an established method that is non-invasive and relatively inexpensive to assess brain function in both healthy and abnormal states in newborn infants (Tharp, Scher et al 1989, Walls-Esquivel, Vecchierini et al 2007, van Putten 2009, Perivier, Roze et al 2016. EEG electrodes, typically placed on the scalp, record the electrophysiological activity of the brain, predominantly of the cerebral cortex (Mizrahi, Hrachovy et al 2004, van Putten 2009, Niedermeyer, Schomer et al 2011.…”
Section: Electroencephalography (Eeg)mentioning
confidence: 99%
“…To my knowledge, this thesis is the first study to investigate the relationship between qEEG and outcomes, both as continuous variables. Most studies focus on the binary classification of visually inspected EEG activity and clinical outcome, i.e., the relationship between normal/abnormal EEG and normal/abnormal clinical outcome (Selton, Andre et al 2013, Perivier, Roze et al 2016. This divides the cohort into sub groups and focuses only on the binary/categorical investigation, i.e., how many infants with abnormal EEG have abnormal outcome, rather than the relationship between EEG and outcome.…”
Section: Strengths Of the Thesismentioning
confidence: 99%